The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/nau.24236
|View full text |Cite
|
Sign up to set email alerts
|

The role of a new three‐dimensional ultrasound technique in the diagnosis of levator ani muscle avulsion

Abstract: Aims: To evaluate the intermethod agreement between the tomographic ultrasound imaging (TUI), considered as the gold standard, and the OmniView-VCI in the diagnosis of levator ani muscle (LAM) avulsion and in the measurement of levator-urethral gap (LUG). Methods:We acquired dynamic 4D transperineal ultrasound volumes from 114 women. Each data set was analyzed on maximal pelvic floor contraction by TUI and OmniView-VCI techniques to check for LAM avulsion. Moreover, we measured LUG using both TUI and OmniView-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It is advocated that the widespread use of imaging has the potential to change the management of pelvic floor morbidity 6–8 . 3D/4D TPU has made it possible to reliably diagnose levator ani muscle (LAM) damage 9,10 . Many studies have found correlations between LAM injuries and pelvic floor dysfunction 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is advocated that the widespread use of imaging has the potential to change the management of pelvic floor morbidity 6–8 . 3D/4D TPU has made it possible to reliably diagnose levator ani muscle (LAM) damage 9,10 . Many studies have found correlations between LAM injuries and pelvic floor dysfunction 11 .…”
Section: Introductionmentioning
confidence: 99%
“…TPU provides an accurate and reproducible tool for the assessment of the pelvic floor dimensions and lesions of the LAM. 5,6,18 Many studies have evaluated the effects of vaginal birth on the pelvic floor. Indeed, LAM avulsion and levator hiatal overdistension are associated with a considerably increased risk of pelvic floor dysfunction, such as pelvic organ prolapse (POP), signs and symptoms of POP and vaginal laxity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that our cutoff of 2.305 cm is the optimal value for our patient population. Montaguti et al 17 compared the OmniView-VCI technique to TUI for diagnosis of Levator avulsion, and found good agreement between the methods with an optimal cutoff value of 2.4 cm on OmniView-VCI method, with a sensitivity of 82% and a specificity of 97%. Had we used the previously published LUG cutoffs on our patient population overall, we would miss a significant number of women who would have gone undiagnosed and possibly prevented from receiving necessary care.…”
Section: Discussionmentioning
confidence: 99%
“…The levator‐urethra gap (LUG) is the distance between the urethral lumen center and the levator insertion site on the inferior pubic rami. Previous studies evaluating LUG measurements have shown different cutoff values for the LUG 1,10,12‐17 . A cutoff of 2.5 cm has been reported in Australian women, 13 while in Chinese women, the cutoff was 2.365 cm 10 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation